Antibody-Mediated Osseous Regeneration for Bone Tissue Engineering in Canine Segmental Defects. (28th February 2018) - Khojasteh, A.; Hosseinpour, S.; Dehghan, M. M.; Mashhadiabbas, F.; Rezai Rad, M.; Ansari, S.; Farzad Mohajeri, S.; Zadeh, H. H.
Abstract : Among many applications of therapeutic monoclonal antibodies (mAbs), a unique approach for regenerative medicine has entailed antibody-mediated osseous regeneration (AMOR). In an effort to identify a clinically relevant model of craniofacial defect, the present study investigated the efficacy of mAb specific for bone morphogenetic protein- (BMP-) 2 to repair canine segmental mandibular continuity defect model. Accordingly, a 15 mm unilateral segmental defect was created in mandible and fixated with a titanium plate. Anorganic bovine bone mineral with 10% collagen (ABBM-C) was functionalized with 25 μ g/mL of either chimeric anti-BMP-2 mAb or isotype-matched mAb (negative control). Recombinant human (rh) BMP-2 served as positive control. Morphometric analyses were performed on computed tomography (CT) and histologic images. Bone densities within healed defect sites at 12 weeks after surgery were 1360.81 ± 10.52 Hounsfield Unit (HU), 1044.27 ± 141.16 HU, and 839.45 ± 179.41 HU, in sites with implanted anti-BMP-2 mAb, rhBMP-2, and isotype mAb groups, respectively. Osteoid bone formation in anti-BMP-2 mAb (42.99% ± 8.67) and rhBMP-2 (48.97% ± 2.96) groups was not significantly different but was higher( p < 0.05 ) than in sites with isotype control mAb (26.8% ± 5.35). In view of the long-term objective of translational application of AMOR in humans, the results of the present study demonstrated the feasibility of AMOR in a large clinically relevant animal model.